Integrative approach to marketing of product and technology lifecycles in innovative and sustainable manufacturing enterprise = Spojrzenie integracyjne na zarządzanie cyklami życia produktui technologii w innowacyjnym i zrównoważonym przedsiębiorstwie produkcyjnym - Gajdzik, Bożena (Zielona Góra: Faculty of Economics and Management Press)
Management of product lifecycle and technology lifecycle should occur in integrated way. Innovative technology achieved in own B+R point or from the surrounding of the enterprise creates conditions to implement new product solutions. The introduction of a new product and new technology must take place in a synchronised way and should take into account the value for the buyer. Moreover, it should not be forgotten that the relationship between the product, technology and the environment is essential in an attempt to reach a state of a sustainable enterprise.
Keywords: cykl życia produktu; cykl życia technologii; innowacje; zrównoważony biznes; product lifecycle; technology lifecycle; innovation; sustainable business